2008
DOI: 10.1111/j.1748-5967.2008.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

External microstructure of the ambrosia beetle Platypus koryoensis (Coleoptera: Curculionidae: Platypodinae)

Abstract: Platypus koryoensis is a minute ambrosia beetle found in forests. It can cause significant economic damage to oak trees. Recently in Korea, it has been reported as a major pest of oak trees, because it causes sooty mold of oak by introducing the pathogenic fungus Raffaelea sp. In this paper, we demonstrate the fine structural aspects of the external body of the ambrosia beetle using field emission scanning electron microscopy, as a part of basic research into this pest so that strategies for its control might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Elytra characteristic of two ambrosia beetles species; A. T. micrurus which collected from Batu, East Java, and B. T. abietis (Buss, 2008). In Platypodines, mycangia are usually more developed in females than males (Kent, 2010) and there are numerous mycangia on the female pronotum such as in P. quercivorus and P. koryoensis (Wood, 1993;Atkinson, 2000;Moon et al, 2008a). On pronotum, mycangia pores can be easily distingushed in T. micrurus females.…”
Section: Resultsmentioning
confidence: 99%
“…Elytra characteristic of two ambrosia beetles species; A. T. micrurus which collected from Batu, East Java, and B. T. abietis (Buss, 2008). In Platypodines, mycangia are usually more developed in females than males (Kent, 2010) and there are numerous mycangia on the female pronotum such as in P. quercivorus and P. koryoensis (Wood, 1993;Atkinson, 2000;Moon et al, 2008a). On pronotum, mycangia pores can be easily distingushed in T. micrurus females.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown by the end of elytra, where elytra of T. abietis has the sharp tip and sharply concave than T. micrurus (Figure 3). In Platypodines, mycangia are usually more developed in females than males (Kent, 2010) and there are numerous mycangia on the female pronotum such as in P. quercivorus and P. koryoensis (Wood, 1993;Atkinson, 2000;Moon et al, 2008a). On pronotum, mycangia pores can be easily distingushed in T. micrurus females.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an exotic ambrosia beetle, Euplatypus parallelus infested Sonokembang trees in southern Thailand (Bumrungsari et al, 2008) and in Malang, Indonesia (Tarno et al, 2014). In addition, other species of ambrosia beetles in the South Asia were reported for Cashew in Goa, India (Marutadurai et al, 2013), while oak ambrosia beetles (Platypus quercivorus and P. Koryoensis) infested Oak tress in Japan and South Korea (Ueda and Kobayashi, 2004;Moon et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…During this survey, we collected suspected specimens of P. quercivorus and P. koryoensis from multiple sites (Figure 1). The senior author identified specimens by comparing the morphological characters with available references (Nobuchi 1973;Hong et al 2006;Moon et al 2008) and identifications were confirmed by Roger Beaver (Chiang Mai, Thailand). One representative specimen of each species has been selected from Yunnan and Jiangxi respectively for molecular diagnosis (P. quercivorus-III, P. koryoensis-III in Table 1).…”
mentioning
confidence: 99%